The Effect of Instagram Marketing and Customer Experience on Customer Loyalty through Customer Engagement in Mili Kopi Pematang Siantar, Indonesia - Siburian, Maretta Selvana; Lubis, Arlina Nurbaity; Situmorang, Syafrizal Helmi (Indonesia Academia Research Society, 2023)
Using social media, such as Instagram, to market products is believed to be more effective and efficient in reaching consumers. The use of social media is closely related to the phenomenon of posting, which is a profitable opportunity for businesses because it can indirectly attract consumers to visit. In addition to social media marketing, creating a good customer experience is crucial as it allows consumers to bond emotionally with the product, ensuring their loyalty. This study aimed to determine and analyze the effect of Instagram Marketing and Customer Experience on customer loyalty, with Customer Engagement as the mediating variable. An associative quantitative method was used with the help of the SPSS program. This research also employed path analysis. The sample of this study consisted of 115 respondents with the criteria of having visited and bought Mili Kopi Café products. The data were collected using questionnaires. The findings suggest that Instagram Marketing and Customer Experience positively affect Customer Loyalty. This study also found that customer engagement is proven to mediate Instagram marketing and customer experience on customer loyalty.